2002
DOI: 10.1046/j.1365-8711.2002.05223.x
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray states and radio emission in GRS 1915+105

Abstract: We have compared simultaneous Ryle Telescope radio and Rossi X-Ray Timing Explorer X-ray observations of the galactic microquasar GRS 1915+105, using the classification of the X-ray behaviour in terms of three states as previously established. We find a strong (one-to-one) relation between radio oscillation events and series of spectrally hard states in the X-ray light curves, if the hard states are longer than ~100s and are "well separated" from each other. In all other cases the source either shows a low-lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
198
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(226 citation statements)
references
References 44 publications
27
198
1
Order By: Relevance
“…This is consistent with the results by Klein-Wolt et al (2002), who find a one-to-one relation between long state C intervals and radio flares, and that these outflow emissions occur shortly after the instability intervals, where we found a loss of matter in the disc.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the results by Klein-Wolt et al (2002), who find a one-to-one relation between long state C intervals and radio flares, and that these outflow emissions occur shortly after the instability intervals, where we found a loss of matter in the disc.…”
Section: Discussionsupporting
confidence: 93%
“…Mirabel et al (1998) reported simultaneous observations in the X-ray, radio and infrared bands, also inferring a possible relation between the IR-radio emissions and the long X-ray dip (state C). Klein-Wolt et al (2002) established a one-to-one relation between the radio flare and the long state C, confirming the connection of the radio jets and the disc instability in GRS 1915+105. Ueda et al (2002) analysed a one week multiwavelength monitoring of GRS 1915+105, that covered a wide energy range from radio to gamma rays.…”
Section: Introductionsupporting
confidence: 65%
“…These sources mirror many properties of AGN (taking into account scaling with the black hole mass) and their emission shows distinct states that are ususally classified as "hard" and "soft" according to their X-ray spectral properties (e.g., Tananbaum et al 1972;Mirabel & Rodriguez 1998, 1999Takeuchi & Mineshige 1998). A possible explanation for this transition (Klein-Wolt et al 2002) is the difference between the ejection of fairly localized knots from the black hole vicinity (leading to X-ray and radio flares) and the ejection of quasi-continuous, extended jets that are initially optically thick (leading to "plateaus" in the X-ray and radio lightcurves). For micro-quasars, these events happen on timescales from minutes (minimum time between the ejection of knots) to tens of days (maximum length of "plateau" phases observed); for AGN, corresponding phenomena would have to occur on timescales of years -thus deviating strongly from a simple linear black-hole mass scaling relation -in order to be consistent with our observations.…”
Section: From Our Test We Can Draw Various Conclusionmentioning
confidence: 88%
“…The plateau state is characterized by a quasi-steady, optically-thick radio emission at the 50-200 mJy level, while the X-ray spectrum is dominated by a hard power-law component (Foster et al 1996;Fender et al 1999). It is sometimes related to one of the canonical states of X-ray binaries, namely the low/hard state (Klein-Wolt et al 2002). This state is preceded and followed by a strong radio flare (Klein-Wolt et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is sometimes related to one of the canonical states of X-ray binaries, namely the low/hard state (Klein-Wolt et al 2002). This state is preceded and followed by a strong radio flare (Klein-Wolt et al 2002). Moreover, just before the post-plateau flare, the X-ray spectrum softens for about 10-20 days (Fender et al 1999;Klein-Wolt et al 2002).…”
Section: Introductionmentioning
confidence: 99%